2023
DOI: 10.1108/ijmf-11-2022-0505
|View full text |Cite
|
Sign up to set email alerts
|

Is corporate digital transformation a tax haven?

Abstract: PurposeCorporate digital transformation (CDT) has challenged traditional tax administration systems. This study examines the impact of CDT on tax avoidance behavior and tests whether tax authorities can identify this behavior.Design/methodology/approachUsing data on listed companies on the Shanghai and Shenzhen Stock Exchanges from 2008 to 2020, this study applies the Heckman two-stage and cross-section models.FindingsThe results show that the higher the degree of CDT, the more aggressive the tax avoidance beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 96 publications
0
1
0
Order By: Relevance
“…In the capital market stream, Wu et al (2022) argued that digital transformation could greatly lower the danger of stock price crashes by lowering information asymmetry, enhancing information transparency, bolstering internal control, enhancing information disclosure, and organizational performance. However, in the taxation stream, Chen and Meng (2023) found a negative association between the degree of corporate digital transformation and tax compliance. Using data from companies listed on the Shanghai and Shenzhen stock exchanges, the study found that the greater the degree of digital transformation, the more aggressive corporate tax avoidance behavior was.…”
Section: Introductionmentioning
confidence: 91%
“…In the capital market stream, Wu et al (2022) argued that digital transformation could greatly lower the danger of stock price crashes by lowering information asymmetry, enhancing information transparency, bolstering internal control, enhancing information disclosure, and organizational performance. However, in the taxation stream, Chen and Meng (2023) found a negative association between the degree of corporate digital transformation and tax compliance. Using data from companies listed on the Shanghai and Shenzhen stock exchanges, the study found that the greater the degree of digital transformation, the more aggressive corporate tax avoidance behavior was.…”
Section: Introductionmentioning
confidence: 91%